Instrumentation and sensors for the food industry - Kress-Rogers, Erika; Brimelow, Christopher J. B. (CRC Press ; Woodhead Pub., 2001)
The first edition of this book quickly established itself as the standard reference in its field, and the second edition consolidates this reputation. Keeping up with the rapid change in this area, there are 16 new contributors and 8 completely new chapters, as well as major revisions to existing chapters, making this second edition a substantially longer book.
Keywords: Food -- Analysis.; Food industry and trade -- Quality control.; Food industry and trade -- Equipment.; Food industry and trade -- Equipment and supplies.; elektronické knihy; electronic books